2020
DOI: 10.1111/1750-3841.15371
|View full text |Cite
|
Sign up to set email alerts
|

Pseudosciaena crocea roe protein‐stabilized emulsions for oral delivery systems: In vitro digestion and in situ intestinal perfusion study

Abstract: Benzyl isothiocyanate (BITC) was encapsulated in oil‐in‐water emulsions stabilized by Pseudosciaena crocea roe protein isolate (PRPI). The stability, lipid digestion, BITC bioavailability, and retention rate of the emulsions were characterized using a simulated gastrointestinal tract model. Tween‐corn and PRPI‐medium‐chain triglycerides (MCT) emulsions were used as controls. The membrane permeability and BITC absorption from these emulsions were investigated by in situ single‐pass intestinal perfusion. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…6(B)). BITC would decompose because of a variety of environmental factors, such as ionic strength and pH 33 . It was suggested that the addition of Alg could enhance the protective effect of FSG against BITC in the gastric digestion environment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6(B)). BITC would decompose because of a variety of environmental factors, such as ionic strength and pH 33 . It was suggested that the addition of Alg could enhance the protective effect of FSG against BITC in the gastric digestion environment.…”
Section: Resultsmentioning
confidence: 99%
“…BITC would decompose because of a variety of environmental factors, such as ionic strength and pH. 33 It was suggested that the addition of Alg could enhance the protective effect of FSG against BITC in the gastric digestion environment. After intestinal digestion, a higher final BITC retention rate in the FSG-Alg emulsion was observed, reaching 85.80% ± 6.55%, compared to only 57.73% ± 8.35% in the FSG emulsion.…”
Section: Interfacial Tension During In Vitro Digestionmentioning
confidence: 99%
“…The aqueous and oil phases were mixed in a ratio of 90:10 ( v/v ), and a coarse emulsion was obtained using a high‐speed disperser (T25; IKA, Staufen, Germany) at 3357 × g for 2 min. The coarsely dispersed emulsion was then homogenized at 600 bar six times using a high‐pressure homogenizer (Panda Plus 2000; GEA Niro Soavi, Italy) 19 . Finally, the FSG concentration of both emulsions was 10 g kg −1 , and the LUT concentration in the FSG–LUT emulsion was 0.6 g kg −1 .…”
Section: Methodsmentioning
confidence: 99%
“…The coarsely dispersed emulsion was then homogenized at 600 bar six times using a high-pressure homogenizer (Panda Plus 2000; GEA Niro Soavi, Italy). 19 Finally, the FSG concentration of both emulsions was 10 g kg −1 , and the LUT concentration in the FSG-LUT emulsion was 0.6 g kg −1 .…”
Section: Emulsion Preparationmentioning
confidence: 98%
“…In addition, the addition of L-cysteine (CYS) effectively prevented BITC from decomposition during 4 °C storage, and the amounts of BITC were maintained during storage for 14 days [5]. In contrast, N- alginate complex, to increase its stability and bioaccessibility [8,9]. Since the poor water solubility, low bioaccessibility, and basic unsteadiness of BITC limit the application of BITC in the food industry, the fish protein-based emulsion system is one of the promising strategies to protect and deliver unstable ITCs due to their non-toxicity, low cost and good accessibility.…”
Section: Instability Of Itcsmentioning
confidence: 99%